2016
DOI: 10.18805/ijar.v0iof.4562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different extenders for preservation of ram semen at 4°C

Abstract: The aim of this study was to investigate the effects of different extenders viz. Tris citric acid fructose egg yolk (TCFEY), Tris citric acid glucose egg yolk (TCGEY), Egg yolk citrate fructose (EYCF) and Egg yolk citrate glucose (EYCG) on the quality of ram spermatozoa during preservation at 4°C. Semen samples showing more than 3+ mass motility and 70% progressive motility were pooled and subsequently divided into four aliquots. Each aliquot was extended separately in four different extenders viz. TCFEY, TCGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…However, the current findings of chilled semen were similar to referred value (> 70%), which is essential for successful artificial insemination (Nilani et al, 2012). The viability in our study of fresh semen was in agreement with the findings of Hassan et al (2009) and, the value for chilled (at 24 and 48 hours) semen was in line with the observation of Rather et al (2017) was to be 85.37 ± 4.19, 82.22±3.26 and 78.36±3.89%, respectively. The sperm viability of chilled semen (10.7h storage) was 60% in small-tail Han sheep (Zhou et al, 2002) that was lower than in the current study.…”
Section: Resultssupporting
confidence: 90%
“…However, the current findings of chilled semen were similar to referred value (> 70%), which is essential for successful artificial insemination (Nilani et al, 2012). The viability in our study of fresh semen was in agreement with the findings of Hassan et al (2009) and, the value for chilled (at 24 and 48 hours) semen was in line with the observation of Rather et al (2017) was to be 85.37 ± 4.19, 82.22±3.26 and 78.36±3.89%, respectively. The sperm viability of chilled semen (10.7h storage) was 60% in small-tail Han sheep (Zhou et al, 2002) that was lower than in the current study.…”
Section: Resultssupporting
confidence: 90%
“…Generally, the current study showed from the commencement to the end of preservation, there was drop in sperm motility from 82% in freshly collected semen to less than 20% at 72 hours post extension for both the extenders. This finding is in agreement with previous studies (Kasimanickam et al, 2011;Rather et al, 2017). Storage temperature, irrespective of diluent, had a significant effect on both motility and viability.…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, the findings from this study suggest that the use of fresh semen shortly after collection and chilled semen at 0 hours and 24 hours post extension could be acceptable for use in artificial insemination (AI) programs in Uda rams. These findings agree with a similar report in Indian indigenous ram by Rather et al (2017). The percentage livability of spermatozoa is important in assessing semen for artificial insemination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation